The art education construction of woven craft society in Kudus Regency (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
One example of society-based local art which is constantly enculturated is woven craft of Desa Jepang (Jepang Village) Kecamatan Mejobo in Kudus Regency. This paper aims at explaining the enculturation of woven craft grown in Jepang village Kudus Regency Central Java Province Indonesia as a form society-based art education. The approach employed in this study was qualitative with the cased study as the research design. Data were collected through observation, non-structural interview, as well as documentation study with interactive model analysis. Research results show that art education grows within the society as the result of enculturation process of woven craft art in Jepang Village that takes place in the forms of: (1) the transmission of the craft skill and (2) the transmission of socio-cultural values. The transmission process is done between the old and young generations both in informal and non-formal ways. The woven craft of Jepang Village as an art product that has been enculturated is unique in terms of its form, media, technique, idea, as well as the modification aspects.